الحرية التعاقدية في الانهاء الدوري للعقد أو امتداده والقيود الواردة عليه - نويري, سعاد (University of Eloued جامعة الوادي, 2022)
إن المبدأ الذي يحكم انقضاء عقود المدة، مؤداه انتهائها تلقائيا بإنقضاء مدتها، والتي لإطرافها حرية تحديدها تطبيقا لقاعدة العقد شريعة المتعاقدين. وامتدت هذه الحرية إلى تقدير ما له من مصلحة في الاستمرار في العلاقة العقدية، وتأجيل انتهاء العقد الأصلي إلى مدة لاحقة يحددانها، أو إنهاء العقد قبل انتهاء مدتها. إن الحق في الإنهاء أو الامتداد، الذي كرسه المشرع بغية توفير حماية لأطرافه، وإقامة توازن عقدي قد أحاطه بجملة من الشروط لضمان هذه الحماية. نبحث في هذا الموضوع شروط وآثار ممارسة مكنة الإنهاء والإمتداد للعقد، ومدى حرية الأطراف في إعمال هذه الحقوق في التأمينات الإجبارية. Abstract: The principle governing the expiry of term contracts is that they expire automatically by expiring, and that they are free to be determined in accordance with the contract rule of contractors. This freedom extended to the appreciation of his interest in continuing the contract relationship, postponing the expiry of the original contract to a later period to be determined, or terminating the contract before its expiry. The right to termination or extension, which the legislator has enshrined in order to provide protection to its parties and to establish a contract balance, has been surrounded by a set of conditions to ensure such protection. We are considering the terms and implications of the practice of the termination and extension of the contract, and the extent to which parties are free to enforce these rights in compulsory insuran
The Contractual Freedom in the Contract Periodic Termination or Extension and its Restrictions
مقال
Keywords: عقود المدة، الإنهاء الدوري للعقد، الامتداد، التأمينات الإجبارية; Term contracts, periodic termination of contract, extension, compulsory insurance.